The Contribution of Learning and Mental Health Variables in First-Year Students' Profiles - Milienos, Fotios S.; Rentzios, Christos; Catrysse, Leen; Gijbels, David; Mastrokoukou, Sofia; Longobardi, Claudio; Karagiannopoulou, Evangelia (Frontiers in Psychology, 2021)
International studies focus on the successful transition into higher education, which is considered crucial for both the students and the educational institution in the context of students’ learning and adjustment in higher education. The aim of the current study was to identify student profiles that include cognitive, metacognitive and motivational aspects of learning, but also aspects of resilience, emotion dysregulation and anxiety. The sample consists of 316 Greek undergraduates students (18.7% males and 81.3% females). The results showed four different (meta)-cognitive-emotional learner profiles: the emotionally stable and highly adaptive learner; the emotionally dysregulated and at risk learner; the emotionally dysregulated and highly adaptive learner; the emotionally stable and at risk learner. Emotionally dysregulated and at risk learner has a lower GPA than the emotional stable and highly adaptive learner, the emotionally dysregulated and highly adaptive learner and the emotionally stable and at risk learner.